'Reading the ads in al-Daʿwa magazine: commercialism and Islamist activism in al-Sadat's Egypt'. Issue 3 (26th May 2020) - Rock-Singer, Aaron; Brooke, Steven
ABSTRACT: This article probes the return of the Muslim Brotherhood to prominence in 1970s Egypt through a systematic analysis of advertisements in the organization's flagship periodical, al-Daʿwa (The Call). In every issue of the magazine, which was published between June 1976 and October 1981, entreaties to proper conduct and appeals to Islamic solidarity appeared alongside advertisements for everything from Pepsi to breakfast biscuits to automobiles. We utilize the methodological insights of social and cultural historians to the value of advertisements to cast new light on the reconstruction of the Brotherhood, its relationship with the diverse institutions comprising the Egyptian state, and on how the Muslim Brotherhood's vision of piety both reflected and challenged a changing economic reality. Moving beyond a story of the Brotherhood's return as a product of independent Islamist enterprise that had emerged due to both the Gulf oil boom and Egypt's economic liberalization programme, significant public sector advertising in al-Daʿwa, especially prominent across the most valuable advertising real estate, underscores both internal divisions within the Egyptian state as well as the tangible ways that various state institutions were patrons of religious change.